Konseptualisasi Agama dan Implikasinya di Indonesia - Aulia Kamal (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
This article discusses how the concept of "religion" is conceptualized in Indonesia and its implications. Through literature review, data was collected and analyzed descriptively, and it was found that: First, the term "religion" is conceptually constructed academically based on the World Religion Paradigm (WRP) with Islam as the model and monotheism as the main feature. Politically, the WRP is increasingly hegemonic through Pancasila, and is constructed in accordance with the policy of religious life from the colonial era to the orde New Order (Orde Baru). Thus, the definition and categorization of religion are stricter and more political. Second, this construction has implications for: (1) Monotheism becoming the standard feature of "recognized religion", making it exclusive and discriminatory. (2) In order to be recognized by the state, Hinduism, Buddhism, and Confucianism are forced to monotheize their theological concepts and submit to Pancasila. (3) The government hastily reduces various local practices to "belief systems". (4) Religion becomes the main identity in citizenship, leading to discrimination and stigmatization of believers of faiths. (5) Academically, the WRP also influences the paradigm in the study of religion. This article recommends the need for a re-identification of religious categories academically, outside of political interests. In addition, it is necessary to distinguish native religions from belief systems because even though they are not identical to world religions, they are not as simple as spiritual practices. Abstrak: Artikel ini mendiskusikan bagaimana kata "agama" dikonseptualisasi di Indonesia dan implikasinya. Melalui studi kepustakaan, data dikumpulkan dan dianalisis secara deskriptif, dan ditemukan bahwa: Pertama, kata “agama” secara konseptual dikonstruksi secara akademis berdasarkan paradigma agama dunia (WRP) dengan Islam sebagai model dan monoteistik sebagai fitur utama. Secara politis, WRP semakin hegemonik melalui Pancasila, lalu dikonstruksi seturut kebijakan kehidupan beragama dari masa kolonial hingga Orde Baru. Jadi definisi dan kategori agama lebih ketat dan politis. Kedua, konstruksi ini berimplikasi pada: (1) Monoteistik menjadi ciri standar pengakuan “agama”, sehingga eksklusif dan diskriminatif. (2) Agar diakui negara, Hindu, Budha, dan Konghucu dipaksa untuk memonoteistifikasi konsep teologinya, tunduk kepada Pancasila. (3) Pemerintah secara gegabah mereduksi berbagai praktik lokal ke dalam "aliran kepercayaan". (4) Agama menjadi identitas utama dalam kewarganegaraan, yang mengarah pada diskriminasi dan stigmatisasi penghayat kepercayaan. (5) Secara akademis, WRP juga mempengaruhi paradigma dalam studi agama. Artikel ini merekomendasikan perlunya identifikasi ulang kategori agama secara akademis, di luar kepentingan politik. Selain itu, perlu membedakan agama pribumi dari aliran kepercayaan karena meskipun tidak identik dengan agama dunia, namun ia tidak sesederhana sebagai praktik kebatinan.